A new cooling strategy for edge computing servers using compact looped heat pipe. (25th March 2021) - Li, Ji; Zhou, Guohui; Tian, Tong; Li, Xingping
Graphical abstract: Highlights: A novel loop heat pipe module was developed for server CPU cooling. Wicks connecting evaporator and condenser were implemented. The 4 mm thick module dissipates 150 W with chip temperature below 85 °C. Tested directions impact the heat transfer performance weakly. Abstract: The rapid development of distributed edge computing system demands urgently that the thermal management solution for server CPUs in micro-data centers have the characteristics of compact structure, high performance, maintenance-free, and energy saving. This paper focuses on a new cooling concept enabled by a compact loop heat pipe. Through removing compensation chamber, selecting a spindle-shaped evaporator structure with aid of an auxiliary gradient sintered capillary wick connecting the condenser and the evaporator, this new proposed loop heat pipe module can provide high reliability operation, meanwhile maintaining high thermal performance. Under forced air cooling, it is demonstrated that the 4 mm thick loop heat pipe module with finned tube condenser could dissipate a heat load of 150 W under a wide fan voltage range from 12 V to 24 V at tested directions when the chip junction temperature was below 85 °C, and could manage a heat load up to 275 W without dry-out. The proposed new loop heat pipe module with finned tube condenser is a potential solution to cool edge-computing server CPUs.